Entre práticas médicas e discursos jurídicos : uma abordagem sobre a reprodução humana assistida no contexto de elaboração do Código Civil de 2002 - Neves, Maurício Vissoto (2009)
It approaches the politician-legislative idea of the delineated context between the years 1970 and 2002 conceming on scientific advances to the attended human being reproduction, focusing itself in the analysis on the referring legal thought to the tradition in addition to the sexuality as estimated the human being reproduction, its repercussions and implications front to the concomitant elaboration period of the new Civil Code. It evaluates the adequacy of the legal system, conducting a comparative analysis between the existent social reality and the idea of legal regulation that presents itself regarding the medication of human reproduction. It analyzes the position of the operators of the legislative politics of Brazil who took part in the elaboration of the related Civil Code and the influences of the existing paradigms in the described period related to the knowledge and adequacy to the new developed scientific techniques. lt is an attempt to identify the strategies oflaw control elaboration in Brazil oft he contextualized period, and to evidence the other face of the politician-institutional relations and its crystallizations in the contemporary world, being used as theoretical perspective the possibility to demonstrate that the ideological consequences of such ideas have not been referring with the scientific advances occurred in the medicine scope, needing reasonable justification face to the imperfection in the main purpose ofthe responsible lnstitutions for the elaboration of laws in Brazil, and in this direction, demonstrate that social happening was not contemplated in the terms where the dominant theoretical proposals presented themselves in the intellectual universe, which the social articulators of the higher stages of appeal were inserted, that is, the legislators. The current advances of the scientific knowledge related to the central subject, considering that are evaluated the direct participation of the human being as research agent and the social phenomena, so that the geneses and the elements reasons that gave the characteristic to the norm in comment - Civil Code of 2002 be understood.